The Influence of Integrated Marketing Communication of Mom's Willingness to Buy - Sariputra, Yoko; Chaldun, Evy Rachmawati (Journal of Innovation, Business and Entrepreneurship, 2017)
Abstract. The largest portion of monthly food expenditure in Indonesia is packaged food and soft drinks that can be found in modern markets. Through the development of this modern market, the demand for processed packaged foods continues to grow which is able to offer time-saving and convenient ways to eat. One of the food packaging companies that produce the packaged food is Sea-Son Company.  This paper will relate one of the business discipline, "Marketing" in Sea-Son Company. Marketing is the main focus of corporate development with the goal of building brand equity and making sales. Since today is the internet area, online digitalization becomes solution for food startup company to support their sales and marketing activity by running Integrated Marketing Communication (IMC) program to achieve company goals. This paper try to research the role of Integrated Marketing Communication (IMC) in attracting target customer and measuring the its effect to customer’s willingness to buy in order to find out the most effective way in attracting households to buy packaged food through online. This research take an descriptive study to measure the IMC of Sea-Son Company which consist of: Ad Facebook promotion; discount coupon; Exhibition; and public relation by social media; and how it affect the mom’s willingness to buy. Data was collected through online questionnaire which distributed to 100 female in Bandung and Jakarta who born between 1970s-1987s who are active internet users and have experience buying instant food through online.The data were analyzed by multi linear regression method to identify the corellation. Empirical results show that, From 4 marketing activities which become the object of the research that are facebook advertisement; discount coupon; trade show; and social media, each has different level of correlation on mom’s willingness to buy. This study is important to the marketers to determine which channel that can  influence mom’s willingness to buy. Marketers could also make improvement and strengthen their business based on selected variable to be more competitive. Keywords: IMC, willingness to buy, packaged food business